Resolving Family Conflicts through Governance : A Case Study of BEZNOSKA, s. r. o. - Kordíková, Lucie; Jurek, Martin; Rosecká, Nikola; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Family businesses are naturally complex systems characterised by the intersection of family, ownership, and business spheres, which often lead to ongoing conflicts and spillover effects. This thesis examines how governance can serve as a framework for resolving family conflicts through an in-depth case study of BEZNOSKA, s. r. o. Employing a mixed-methods approach, the study combines qualitative thematic analysis of semi-structured interviews with a quantitative assessment of sixteen conflict areas derived from academic literature. Conflict magnitude and cross-system spillovers are analysed using descriptive statistics and subsequently visualised through a conflict intensity heatmap and a conflict mapping matrix. The empirical findings emphasise the importance of clearer role definitions, structured communication channels, and the gradual integration of governance mechanisms to stabilise decision-making processes and reduce cross-system conflict dynamics.
Vedoucí práce: Martin Jurek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses